A highly selective quinolizinium-based fluorescent probe for cysteine detection. Issue 53 (11th October 2021) - O, Wa-Yi; Chan, Wing-Cheung; Xu, Caifeng; Deng, Jie-Ren; Ko, Ben Chi-Bun; Wong, Man-Kin
Abstract : A novel fluorescent quinolizinium-based turn-off probe for selective detection of cysteine has been developed. Abstract : A novel fluorescent quinolizinium-based turn-off probe has been developed for selective detection of cysteine. The probe showed high selectivity and sensitivity towards cysteine over other amino acids including the similarly structured homocysteine and glutathione with a detection limit of 0.18 μM (S/N = 3). It was successfully applied to cysteine detection in living cells with low cytotoxicity and quantitative analysis of spiked mouse serum samples with moderate to good recovery (96–109%).